2017
DOI: 10.1161/circimaging.116.006249
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Cross-Sectional Area/Height Ratio and Outcomes in Patients With Bicuspid Aortic Valve and a Dilated Ascending Aorta

Abstract: Background— In patients with bicuspid aortic valve and dilated proximal ascending aorta, we sought to assess (1) factors associated with increased longer-term cardiovascular mortality and (2) incremental prognostic use of indexing aortic root to patient height. Methods and Results— We studied 969 consecutive bicuspid aortic valve patients (50±13 years; 87% men) with proximal aorta ≥4 cm, who also had a gated contrast-enhanced thoracic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Considering the indexed areas and the follow-up measurements from the current study, four patients in this population would be identified to be at risk of aortic dissection and requiring intervention, with area >10 cm 2 /m and 48–50 mm diameter 21 29. It should also be noted that our population is relatively young (average age 39 years overall) and while we cannot extrapolate information on growth rate beyond the time window that was studied, we cannot exclude further aortic dilation in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the indexed areas and the follow-up measurements from the current study, four patients in this population would be identified to be at risk of aortic dissection and requiring intervention, with area >10 cm 2 /m and 48–50 mm diameter 21 29. It should also be noted that our population is relatively young (average age 39 years overall) and while we cannot extrapolate information on growth rate beyond the time window that was studied, we cannot exclude further aortic dilation in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…If the maximal TAA cross-sectional area (in cm 2 ) divided by height (in meters) is greater than 10, this would be another indication for intervention. 2 This threshold was derived from studies from Cleveland Clinic originally applied to patients with bicuspid aortic valves and Marfan syndrome, 19,20 and more recently in all TAA patients, 21 with major prognostic implications (Figure 4).…”
Section: Another Indication For Intervention Is a Maximal Cross-sectimentioning
confidence: 99%
“…Any proximal aortic disease that is associated with a maximum aortic diameter > 40 mm and/or an indexed aortic diameter exceeding 21 mm/m 2 , respectively, is defined as aortopathy [ 9 ]. Other authors postulated the benefit of using indexed aortic area (i.e., aortic root or ascending aorta area divided by the body height) to define a clinically-relevant aortopathy [ 10 ].…”
Section: Bav–the Clinical Perspectivementioning
confidence: 99%